Assessment of the Development and Growth of Nigerian Economy as a Function of FDI Flows - Mokuolu, Joseph Oluseye (Journal of Accounting, Business and Finance Research, 2018)
An attempt is made to postulate a model based on the assumption that the inflow of Foreign Direct Investment (FDI) affect the growth of Nigerian economy. A simple econometric modeling approach was applied to time series annual Nigerian data for a period covering forty eight years. The result revealed that there exist a strong positive relationship between FDI flows and economic growth represented by the Gross Domestic Product (GDP). The implication of this is that the inflows of FDI reasonably affect the level of growth of the economy with the level of correlation and the positive sign between the two variables. The study concluded that FDI is germane to the economic development of a developing country and on the basis of the findings it is recommended that a positive step should be taken to encourage indigenous companies to understudy and learn the process and strategies of the MNCs.